Commercial Dispute Resolution: Has Arbitration Transformed Nigeria’s Legal Landscape? - OLUJOBI, Olusola Joshua; ADENIJI, Adenike A.; OYEWUNMI, Olabode A.; OYEWUNMI, Adebukola E. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).25, 2018)
The adoption of arbitration in the light of its well established attributes promotes confidence levels in the general businesses environment, enhances institutional trust, whilst also developing practical compromise resolution mechanisms. However, Nigeria, a developing economy has not matched policy intent with commercial realities, particularly in terms of broad based integration and utilization of arbitral tools. This trend is not sustainable in the light of the renewed efforts to promote enhanced justice delivery; lower administrative costs and the urgent need to optimize the capabilities of the judicial arm of government. The paper assessed specific arbitral provisions of selected, State High Court Civil Procedures Rules, and on this basis critiqued the arbitral visibility and incorporation relative to established legal processes. Amongst other salient issues, a robust application of arbitration is recommended especially in view of the peculiarities of Nigeria’s legal processes, judicial institutions, evolving political and social-economic indicators.